A structural study of the interaction between the Dr haemagglutinin DraE and derivatives of chloramphenicol. - Pettigrew, D; Roversi, P; Davies, S; Russell, A; Lea, S (2009)
Dr adhesins are expressed on the surface of uropathogenic and diffusely adherent strains of Escherichia coli. The major adhesin subunit (DraE/AfaE) of these organelles mediates attachment of the bacterium to the surface of the host cell and possibly intracellular invasion through its recognition of the complement regulator decay-accelerating factor (DAF) and/or members of the carcinoembryonic antigen (CEA) family. The adhesin subunit of the Dr haemagglutinin, a Dr-family member, additionally binds type IV collagen and is inhibited in all its receptor interactions by the antibiotic chloramphenicol (CLM). In this study, previous structural work is built upon by reporting the X-ray structures of DraE bound to two chloramphenicol derivatives: chloramphenicol succinate (CLS) and bromamphenicol (BRM). The CLS structure demonstrates that acylation of the 3-hydroxyl group of CLM with succinyl does not significantly perturb the mode of binding, while the BRM structure implies that the binding pocket is able to accommodate bulkier substituents on the N-acyl group. It is concluded that modifications of the 3-hydroxyl group would generate a potent Dr haemagglutinin inhibitor that would not cause the toxic side effects that are associated with the normal bacteriostatic activity of CLM.